Dynamic Modelling Analysis on The Effectiveness of Coastal Land Resources for Aquaculture Activities Utilization - Ariadi, Heri; Madusari, Benny Diah; Mardhiyana, Dewi (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2024)
Coastal areas are considered biodiversity zones. This study aimed to analyze the effectiveness of land use on aquaculture productivity rate in coastal areas using a dynamic modeling analysis system. This study was conducted in the Pekalongan Province. Water quality parameters and qualitative research data were obtained from an in-depth survey. Furthermore, the data were analyzed using dynamic modeling analysis. The results of this study indicate that the level of coastal land use has a variable relationship with the productivity rate of aquaculture. Based on the causal loop model, it could be analyzed that the social, environmental conditions in coastal areas were described as continuing to experience quantification of population increase and environmental utilization rates. Overall, the productivity level of aquaculture cultivation in coastal areas tended to decrease along with the increasing value of productive land use accompanied by increased inputs and the number of human resource populations in coastal areas. The optimal inclusion of this study was that the optimal land use level would impact the productivity management level of aquaculture cultivation in coastal areas. Based on the results of this study, it can be concluded that the optimal utilization of coastal land greatly impacted the management of the productivity level of aquaculture cultivation, which was carried out in an integrated manner. Furthermore, the analysis of the dynamic modeling system also illustrated the increasing social-environmental conditions in coastal land utilization.